Combustion of Diesel and Syngas Mixtures in a 2-Stroke Diesel Engine - Eva Sarah Bt Zakaria, Eva Sarah (Universiti Teknologi Petronas, 2010)
Biomass is fast becoming the new era of technology due to the reduction of fossil fuel in the coming generation. Biomass can be converted to useful materials through the process of gasification. This process will in turn produce syngas or producer gas. Syngas can be used in many applications such as to produce methanol as well as to generate electricity. This study focuses on the application of syngas in internal combustion engine to generate power. Researchers have studied that there is a fluctuation of syngas produced from gasification process.